2019
DOI: 10.1016/j.seizure.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between high titers of glutamic acid decarboxylase antibody and epilepsy in patients with type 1 diabetes mellitus: A cross-sectional study

Abstract: Individuals with type 1 diabetes mellitus (T1D) are at higher risk of epilepsy. T1D is a progressive immune-mediated disease and the etiology of epilepsy remains unknown in most. Glutamic acid decarboxylase (GAD) catalyzes GABA formation. GABA-secreting neurons and pancreatic beta cells are the major cells expressing GAD. Methods: Cross-sectional study. Patients with T1D from a multiethnic population underwent GADA measurement to investigate possible association between T1D and epilepsy of unknown etiology. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…High GAD65-Ab levels (at least 100-fold) have been found in autoimmune neurological disorders (e.g., stiff-person syndrome, cerebellar ataxia, and limbic encephalitis), sporadic drug-resistant temporal lobe epilepsy in children and adults, and in the subgroup of patients with T1DM who develop seizures. Low levels might promote both T1DM and seizures, even though further studies are needed to support this hypothesis [ 153 , 154 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
“…High GAD65-Ab levels (at least 100-fold) have been found in autoimmune neurological disorders (e.g., stiff-person syndrome, cerebellar ataxia, and limbic encephalitis), sporadic drug-resistant temporal lobe epilepsy in children and adults, and in the subgroup of patients with T1DM who develop seizures. Low levels might promote both T1DM and seizures, even though further studies are needed to support this hypothesis [ 153 , 154 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is a bidirectional epidemiologic link between epilepsy with neuropsychiatric symptoms and systemic autoimmune diseases: patients with epilepsy present a higher risk for developing systemic autoimmune disease and vice versa [ 5 , 142 - 145 ]. Several mechanisms are claimed to explain this intriguing association, like genetic status, innate or adaptative arms of the immune system with CNS involvement [ 5 , 154 , 162 , 188 , 195 , 197 , 205 ]. This review highlights the comorbidity between seizures and neuropsychiatric features in SLE, emphasizing NPSLE, T1DM, CD and HT.…”
Section: Discussionmentioning
confidence: 99%
“…In T1DM animal models with seizures, there are increased serum levels of cytokines and a more profound BBB dysfunction [ 187 ]. Concerning the role of the adaptive immune system, GAD65 antibodies were considered a risk factor for the development of seizures or neuropsychiatric symptoms in T1DM patients [ 188 ]. Furthermore, GAD-related epilepsy was also considered a distinct clinical picture with autoimmune epilepsy or encephalitis, in which immunotherapy can be effective if administered early, preventing permanent brain damage [ 189 ].…”
Section: Systemic Autoimmune Diseases and Epilepsymentioning
confidence: 99%
“…Notably, recent research indicates a potential heightened susceptibility among patients with type 1 diabetes to several neurocognitive disorders 9,10 , including epilepsy 11 . Several observational studies have indicated a potential overrepresentation of epilepsy in individuals with type 1 diabetes [12][13][14][15] , although the findings have not always been consistent 16 . Moreover, the potential elevated risk of the development of epilepsy among individuals with type 1 diabetes in comparison with those with normoglycemia remains uncertain.…”
Section: Introductionmentioning
confidence: 99%